The Use of Timetable Learning Media to Enhance Student Engagement in Mathematics for Grade II A at Baiturrohman GMI Jember Elementary School - Amalia, Rizki; Hasanah, Robiatul (IJIE International Journal of Islamic Education, 2023)
This research is a qualitative study that explores the use of a timetable board as a learning tool to enhance student engagement in Mathematics, specifically the topic of time units, for Grade II A students at Baiturrohman GMI Jember Elementary School. The objectives of this study are to determine 1) The process of using the timetable board in teaching Mathematics, focusing on time units, for Grade II A students at this school, and 2) The improvement of student engagement in Mathematics, particularly in the topic of time units, through the use of the timetable board in Grade II A at this school. The data collection techniques include lectures (material delivery), observation, discussion, tests, and documentation. The subjects of this study are 18 students in Grade II A. The implementation of the learning activities using the timetable board as a teaching aid is deemed successful due to the students' significant curiosity during the learning process. This curiosity has led to increased student activity during the learning process, with a majority of students showing a 50% improvement in understanding the material related to time units in Mathematics. In conclusion, this research suggests that using the timetable board as a learning tool effectively enhances student engagement in Mathematics, particularly in the topic of time units, for Grade II a students at this Elementary School.